Isolated atrial amyloid contains atrial natriuretic peptide: a report of six cases. Issue 4 (October 1986) - Kaye, G C; Butler, M G; d'Ardenne, A J; Edmondson, S J; Camm, A J; Slavin, G
Abstract : Twenty five specimens of the human right atrial appendage were examined for immunoreactivity to alpha human atrial natriuretic peptide. In the electron microscope characteristic amyloid fibrils were identified around small blood vessels and adjacent to atrial muscle cells in eight of the surgical cases and in two necropsy cases. In six cases, four surgical and two necropsy, these fibrils contained immunoreactive alpha human atrial natriuretic peptide. Amyloid is known to occur in peptide secreting endocrine tumours and immunoreactive peptide may be incorporated in the amyloid matrix. The demonstration of atrial amyloid containing immunoreactive alpha human atrial natriuretic peptide suggests that some deposits of cardiac amyloid are of a type analogous to that found in other endocrine organs.